Pengaruh Financial Attitude, Financial Knowledge, Dan Financial Self-Efficacy Terhadap Financial Management Behavior - Hamid, Saina; Hasan, Muhammmad Hi; Ruray, Titiek Arafiani; toduho, Mustafa K (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the influence of financial attitude, financial knowledge, and financial self-efficacy on financial management behavior among micro business actors in the culinary sector in South Tidore District, Tidore Islands City. This study uses a quantitative method with a population of 77 culinary businesses in South Tidore District. The results of the study indicate that the variable financial attitude does not have a positive and significant effect on financial management behavior, as indicated by a coefficient value of -0.09, with a t-value of 0.884 > t-table 1.666 and a significance level of 0.377 > 0.05. Financial knowledge has a positive and significant effect on financial management behavior, as indicated by a coefficient value of 0.771 with a t-value of 11.326 > t-table 1.666 and a significance level of 0.000 < 0.05. Financial self-efficacy also has a positive and significant effect on financial management behavior, as shown by a coefficient value of 0.177 with a t-value of 2.866 > t-table 1.666 and a significance level of 0.005 < 0.05. Simultaneously, financial attitude, financial knowledge, and financial self-efficacy have a significant effect on financial management behavior, proven by an F-value of 165.944 > F-table 2.730 and a significance level of 0.000 < 0.05.